2021
DOI: 10.1101/2021.10.06.463337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Progesterone supplementation in mice leads to microbiome alterations and weight gain in a sex-specific manner

Abstract: BackgroundProgesterone is a steroid hormone produced by the ovaries, involved in pregnancy progression and necessary for successful gestation. We have previously shown that progesterone affects gut microbiota composition and leads to increased relative abundance of Bifidobacterium.ResultsIn non-pregnant female GF mice, levels of progesterone were significantly higher than in SPF mice of the same status. However, no significant differences were observed between GF and SPF males. Females treated with progesteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This is further supported by evidence showing that administering progesterone to women with a history of PTBs and a high risk of recurrence can decrease the likelihood of another PTB by 33% [ 54 ]. Another research conducted by Nuriel‐Ohayon et al revealed that administering progesterone alters the gut microbiome in females, resulting in weight gain, an effect replicable in germ‐free mice through fecal transplant [ 55 ]. These findings illustrate a complex interaction between gut microbiota and progesterone.…”
Section: Interregulation Of Gut Microbiota and Pregnancy‐related Horm...mentioning
confidence: 99%
“…This is further supported by evidence showing that administering progesterone to women with a history of PTBs and a high risk of recurrence can decrease the likelihood of another PTB by 33% [ 54 ]. Another research conducted by Nuriel‐Ohayon et al revealed that administering progesterone alters the gut microbiome in females, resulting in weight gain, an effect replicable in germ‐free mice through fecal transplant [ 55 ]. These findings illustrate a complex interaction between gut microbiota and progesterone.…”
Section: Interregulation Of Gut Microbiota and Pregnancy‐related Horm...mentioning
confidence: 99%